Skola i modernitet - Frykman, Jonas (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
This paper concentrates on the mimetical of modernity in schools in 20th century Sweden. Up to the last twenty years, schooling more or less demanded a change in bodily habitus. Boys especially had to reorganize their mimetical relation to fathers and friends. They represented masculine ideals founded upon the immediate surroundings and action. Their, on the other hand, was an identity of "becoming": reflexivity and literacy had to be incorporated. Schools were the most important arenas for learning transcendence. Bodily mastery in gymnastics as well as in the ritual relation to knowledge organized body and soul, set off school from the rest of social life. A different phase in modernity was marked off when education became centered on the individual, when knowledge and discourse no longer organized bodies. Boys had no need to mimetically distance themselves from the premodern setting of home. Their backgrounds were taken along to school, not transcended. Today social mobility by the means of schooling is considerably slowing down. Schooling has become a booster of — not an alternative to — home and social background.